2020
DOI: 10.1177/0269216320963941
|View full text |Cite
|
Sign up to set email alerts
|

Tools to help healthcare professionals recognize palliative care needs in patients with advanced heart failure: A systematic review

Abstract: Background: The delivery of palliative care interventions is not widely integrated in chronic heart failure care as the recognition of palliative care needs is perceived as difficult. Tools may facilitate healthcare professionals to identify patients with palliative care needs in advanced chronic heart failure. Aim: To identify tools to help healthcare professionals recognize palliative care needs in patients with advanced chronic heart failure. Design: This systematic review was registered in the PROSPERO dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 61 publications
0
17
0
3
Order By: Relevance
“…The methodology for the identification of the tools was described elsewhere. 18 Besides existing tools related to CHF, the Support Needs Approach for Patients needs assessment tool to identify palliative support needs in advanced chronic obstructive pulmonary disease (COPD) was used to identify promising questions. 22…”
Section: Stage 1a: Systematic Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…The methodology for the identification of the tools was described elsewhere. 18 Besides existing tools related to CHF, the Support Needs Approach for Patients needs assessment tool to identify palliative support needs in advanced chronic obstructive pulmonary disease (COPD) was used to identify promising questions. 22…”
Section: Stage 1a: Systematic Reviewmentioning
confidence: 99%
“…The content of the tool elaborates on existing content and criterion validation research of tools in the context of PC and advanced CHF and on the lessons learnt from practice. 18 Moreover, the care recommendations are partly based on the Dutch multidisciplinary guideline 'PC for patients with heart failure'. 32…”
Section: Strengths Of I-harpmentioning
confidence: 99%
See 2 more Smart Citations
“…These tools used as a support and a starting point for delivering patient-centered care [ 6 ]. Two recent systematic reviews found six needs measurement tools that can be used with patients with HF [ 6 , 7 ]. Both systematic reviews found that the most comprehensive of these tools and the only one created specifically for patients with HF is the “Needs Assessment Tool: Progressive Disease-Heart Failure” (NAT: PD-HF) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%